VULNERACIÓN Y CRIMINALIZACIÓN DEL DERECHO A LA RESISTENCIA CONSAGRADO EN EL ARTÍCULO 98 DE LA CONSTITUCIÓN DE LA REPÚBLICA DEL ECUADOR - Rivera Jiménez., Kevin Daniel (2019)
This research paper is entitled "Violation and criminalization of the right to resistance enshrined in article 98 of the Constitution of the Republic of Ecuador", which arises from the perspective and analysis carried out both in the Constitution of the Republic of Ecuador in its article 98 that establishes: "The individuals and collectives will be able to exercise the right to resistance against actions or omissions of the public power or of the natural or juridical non-State persons that violate or could violate their constitutional rights, and to demand the recognition of new rights". We can thus demonstrate that this right has been violated and criminalized through the crimes of sabotage and paralysis of a public service stipulated in articles 345 and 346, respectively, of the Comprehensive Organic Penal Code. As our investigation progresses, we will address the fact that the right to resistance that citizens and collectives have has been violated and criminalized, attributing to the people who employed it, conduct of a criminal nature, so that Ecuadorian citizens who felt affected in their rights by provisions issued by the government saw the need to exercise the right to resistance, which is the most passive way of claiming and being heard by government authorities, However, the response was not the same since they were prosecuted for the criminal types of sabotage and paralysis of a public service in which there is already fraudulent conduct contrary to the resistance as such but which the judicial operators do not consider at the time of judging. Therefore, for the faithful fulfillment of the proposed objectives, I proceeded to make a theoretical, legal and doctrinal conglomerate as well as an essential part such as comparative legislation and field research in relation to the violation and criminalization of the right to resistance. In the same way, the application of methods and techniques 5 such as the survey and the interview that was directed towards legal professionals with which I was able to obtain concrete results and criteria, from which clear and concise foundations are derived for the proposal of necessary reforms to solve this problem. With all the aspects described above and that are studied in the present work, that in its final part establishes the proposal of a juridical proposal according to the current juridical reality, directed to the respect of the mandates established in the Constitution, being the right to the resistance a fundamental pillar of the free expression of the Ecuadorian citizens and as the form to respond before the dispositions emitted by authorities of government of which they are affected, guaranteeing the fulfillment of this right at the moment of considering the attribution of criminal type with what we assure a fair resolution where the punitive or sanctioning power, that is to say, on the part of the operators of justice is respecting the rights and constitutional guarantees.